Learning media free fall motion to reduce misconceptions and improve students' understanding of the concept. Issue 3 (February 2019) - Firdaus, T; Erwin, E; Rosmiati, R
Abstract: Has been made free fall learning media for class X students in Physics subjects. Students always think that the amount of mass affects the acceleration of vertical falling objects downward. Media was created to reduce student misconceptions. This research uses demonstration method. This media is proven to reduce misconceptions and can improve students' conceptual understanding.